1.
If f(x) = x^2 - 2x + 1, what is f(1)?
Correct Answer
C. 0
Explanation
To find f(1), we substitute 1 into the function f(x) = x^2 - 2x + 1. So, f(1) = 1^2 - 2(1) + 1 = 1 - 2 + 1 = 0. Therefore, the answer is 0.
2.
If the side of a square is of length (x + 5), what is its area?
Correct Answer
C. X^2 + 10x + 25
Explanation
The area of a square is equal to the side length squared. In this case, the side length is (x + 5), so the area of the square is (x + 5)^2. Expanding this expression gives us x^2 + 10x + 25. Therefore, the correct answer is x^2 + 10x + 25.
3.
If f(x) = 1/(x - 1) what is f(0)?
Correct Answer
C. -1
Explanation
The function f(x) is defined as 1/(x-1). To find f(0), we substitute 0 into the function for x. Therefore, f(0) = 1/(0-1) = 1/(-1) = -1.
4.
What is the graph of y = 7x - 1?
Correct Answer
A. A Line
Explanation
The equation y = 7x - 1 represents a linear function, where the graph is a straight line. The coefficient of x is 7, indicating that for every increase of 1 in x, y will increase by 7. The constant term -1 indicates that the line will intersect the y-axis at -1. Therefore, the graph of y = 7x - 1 is a line.
5.
What value of y makes y/(-10) = 100 a true statement?
Correct Answer
B. -1000
Explanation
To find the value of y that makes the equation true, we can solve for y by multiplying both sides of the equation by -10. This gives us y = 100 * -10 = -1000. Therefore, the value of y that makes the equation true is -1000.
6.
What is 1/6 in decimal form?
Correct Answer
D. 0.1666
Explanation
The correct answer is 0.1666 because when we divide 1 by 6, we get a repeating decimal of 0.1666.
7.
What values of x make (2x - 3)(3x + 1) = 0 a true statement?
Correct Answer
D. 3/2 And -1/3
Explanation
To find the values of x that make the given statement true, we need to solve the equation (2x - 3)(3x + 1) = 0. This equation will be true if either of the factors equals zero. Setting 2x - 3 = 0, we can solve for x to find x = 3/2. Setting 3x + 1 = 0, we can solve for x to find x = -1/3. Therefore, the values of x that make the statement true are 3/2 and -1/3.
8.
What is x^3 - x in factored form?
Correct Answer
D. X(x - 1)(x + 1)
Explanation
The given expression, x^3 - x, can be factored as x(x - 1)(x + 1). This can be determined by looking for common factors and using the distributive property. The expression can be rewritten as x(x^2 - 1), and then further factored as x(x - 1)(x + 1) by recognizing the difference of squares pattern.
9.
What is the area of a trapezoid that has bases of 10 feet and 14 feet and a height of 8 feet?
Correct Answer
A. 96 Square Feet
Explanation
The area of a trapezoid is calculated by multiplying the average of the lengths of the bases by the height. In this case, the average of the lengths of the bases is (10 + 14) / 2 = 12 feet. Multiplying this by the height of 8 feet gives us an area of 12 * 8 = 96 square feet.
10.
What is the x-intercept of 4x + 2y = -8?
Correct Answer
B. (-2, 0)
Explanation
The x-intercept of a linear equation represents the point where the line crosses the x-axis. To find the x-intercept, we set y = 0 and solve for x. In this equation, if we substitute y = 0, we get 4x + 2(0) = -8, which simplifies to 4x = -8 and x = -2. Therefore, the x-intercept is (-2, 0).
11.
If x = 1, what is y = 2^x?
Correct Answer
A. 2
Explanation
When x is equal to 1, the equation y = 2^x can be simplified as y = 2^1, which is equal to 2. Therefore, the value of y is 2 when x is 1.
12.
How much interest is earned if $2500 is invested for 25 years at 8% simple interest?
Correct Answer
D. 5000
Explanation
If $2500 is invested for 25 years at 8% simple interest, the interest earned can be calculated using the formula: Interest = Principal * Rate * Time. Plugging in the values, we get: Interest = $2500 * 0.08 * 25 = $5000. Therefore, the correct answer is 5000.
13.
If x = -4 and y = 5, what is (x^4)*(y^2)?
Correct Answer
B. 6400
Explanation
When we substitute the given values of x = -4 and y = 5 into the expression (x^4)*(y^2), we get (-4^4)*(5^2). Simplifying this, we have (256)*(25) which equals 6400. Therefore, the correct answer is 6400.
14.
What is 5(4x - 1) + 9x when simplified?
Correct Answer
B. 29x - 5
Explanation
To simplify the expression 5(4x - 1) + 9x, we need to distribute the 5 to both terms inside the parentheses. This gives us 20x - 5 + 9x. Combining like terms, we get 29x - 5. Therefore, the correct answer is 29x - 5.
15.
If x = 0, what is y = 2^x?
Correct Answer
D. 1
Explanation
When x is equal to 0, any number raised to the power of 0 is equal to 1. Therefore, when x = 0, y = 2^0 = 1.